GPS measurements of postseismic deformation due to October 8, 2005 Kashmir earthquake - Reddy, C. D.; Prajapati, Sanjay K. (My University, 2009)
Relaxation of the coseismic stresses following an earthquake causes postseismic crustal deformation, which can last for days to years. Continuous monitoring of postseismic deformation facilitates the understanding of the mechanism of deformation and postseismic relaxation and viscous rheology. After the October 8, 2005 Kashmir earthquake, global positioning system data for 8 months, starting from October, 2005 have been analyzed from three continuous sites located at Gulmarg, Amritsar, and Jaipur. The average velocity during the observation period at Gulmarg (8.6 cm/year) is significantly higher than the Indian plate velocity exhibiting postseismic crustal deformation. The velocity at Amritsar (5.9 cm/year) and Jaipur (5.1 cm/year) is comparable to the Indian plate velocity. At Gulmarg, the logarithmic function fits well to the north–south component of postseismic transients (~in the coseismic slip direction). The nature of decay in these transients suggests that the deformation is mainly due to an afterslip, and the second possible contribution may be from the viscous relaxation process. This paper presents the characteristics of postseismic transients and possible contributions from various postseismic mechanisms subsequent to the Kashmir earthquake.
Keywords: Global Positioning System; Postseismic deformation; Logarithmic decay; Afterslip; Kashmir earthquake